Large gains in schooling and income are possible from minimizing adverse birth outcomes in 121 low- and middle-income countries: A modelling study. - Mia M Blakstad; Nandita Perumal; Lilia Bliznashka; Mark J Lambiris; Günther Fink; Goodarz Danaei; Christopher R Sudfeld (Public Library of Science (PLoS), 2022)
While the global contributions of adverse birth outcomes to child morbidity and mortality is relatively well documented, the potential long-term schooling and economic consequences of adverse birth outcomes has not been estimated. We sought to quantify the potential schooling and lifetime income gains associated with reducing the excess prevalence of adverse birth outcomes in 121 low- and middle-income countries. We used a linear deterministic model to estimate the potential gains in schooling and lifetime income that may be achieved by attaining theoretical minimum prevalence of low birthweight, preterm birth and small-for-gestational age births at the national, regional, and global levels. We estimated that potential total gains across the 121 countries from reducing low birthweight to the theoretical minimum were 20.3 million school years (95% CI: 6.0,34.8) and US$ 68.8 billion (95% CI: 20.3,117.9) in lifetime income gains per birth cohort. As for preterm birth, we estimated gains of 9.8 million school years (95% CI: 1.5,18.4) and US$ 41.9 billion (95% CI: 6.1,80.9) in lifetime income. The potential gains from small-for-gestational age were 39.5 million (95% CI: 19.1,60.3) school years and US$113.6 billion (95% CI: 55.5,174.2) in lifetime income gained. In summary, reducing the excess prevalence of low birthweight, preterm birth or small-for-gestational age births in low- and middle-income countries may lead to substantial long-term human capital gains in addition to benefits on child mortality, growth, and development as well as on risk of non-communicable diseases in adults and other consequences across the life course.